The intervention of curcumin on rodent models of hepatic fibrosis: A systematic review and meta-analysis. - Yun-Hang Chu; Bing-Yao Pang; Ming Yang; Qi Meng; Yan Leng (PLoS ONE)
Objective This study aimed to evaluate the intervention effect of curcumin on hepatic fibrosis in rodent models through systematic review and meta-analysis, in order to provide meaningful guidance for clinical practice. Methods A systematic retrieval of relevant studies on curcumin intervention in rats or mice hepatic fibrosis models was conducted, and the data were extracted. The outcome indicators included liver cell structure and function related indicators, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), albumin (ALB), ratio of albumin to globulin (A/G), total bilirubin (TBIL), bax protein, bcl-2 protein and index of liver, as well as the relevant indicators for evaluating the degree of hepatic fibrosis, such as hyaluronic acid (HA), laminin (LN), type I collagen (Collagen I), type III collagen (Collagen III), type III procollagen (PCIII), type III procollagen amino terminal peptide (PIIINP), type IV collagen (IV-C), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), α-Smooth muscle actin (α-SMA), hydroxyproline (HYP), platelet derived factor-BB (PDGF-BB), connective tissue growth factor (CTGF) and transforming growth factor-β1 (TGF-β1), and oxidative stress-related indicators, such as superoxide dismutase (SOD), malondialdehyde (MDA) and glutathione peroxidase (GSH-Px). These results were then analyzed by meta-analysis. Studies were evaluated for methodological quality using the syrcle's bias risk tool. Results A total of 59 studies were included in the meta-analysis, and the results showed that curcumin can reduce the levels of ALT, AST, ALP, TBIL, bax protein, and index of liver in hepatic fibrosis models. It can also reduce HA, LN, Collagen I, Collagen III, PCIII, PIIINP, IV-C, TNF-α, α-SMA, HYP, PDGF-BB, CTGF, TGF-β1 and MDA, and increase the levels of ALB, A/G, SOD, and GSH-Px in the hepatic fibrosis models. However, the effects of curcumin on bcl-2 protein, IL-6 in hepatic fibrosis models and index of liver in mice were not statistically significant. Conclusion The analysis results indicate that curcumin can reduce liver cell apoptosis by maintaining the stability of liver cell membrane, inhibit the activation and proliferation of hepatic stellate cells by reducing inflammatory response, and alleviate tissue peroxidation damage by clearing oxygen free radicals.